2008
DOI: 10.1074/jbc.m801210200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Co-translocation of Myotrophin and p65 Stimulates Myocyte Growth

Abstract: Myotrophin, a 12-kDa ankyrin repeat protein, stimulates protein synthesis and cardiomyocyte growth to initiate cardiac hypertrophy by activating the NF-B signaling cascade. We found that, after internalization into myocytes, myotrophin cotranslocates into the nucleus with p65 to stimulate myocyte growth. We used structure-based mutations on the hairpin loops of myotrophin to determine the effect of the loops on myotrophin and p65 localization, induction of protein synthesis, and cardiac hypertrophy. Loop mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…Neonatal rat (Rattus norvegicus) ventricular cardiomyocytes were isolated from 3-to 4-day-old American Wistar rat pups according to the procedure described by Sen et al 10 2.4 Confocal imaging to detect activation of p53 by myo and quantitation of cell surface area Isolated rat neonatal ventricular myocytes were stimulated with myo and 5-fluorouracil (5-FU, a potent activator of p53) 18 for 24 h; cell fixation and permeabilization and confocal imaging was performed as described previously 12,19 (see Supplementary material online, Methods). Stimulation of cardiomyocytes with 100 nm Angiotensin II (Sar 1 ) 20 was performed as positive control for the measurement of cell surface area using Image-Pro Plus 6.1 software (see Supplementary material online, Methods).…”
Section: Preparation Of Neonatal Rat Ventricular Myocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal rat (Rattus norvegicus) ventricular cardiomyocytes were isolated from 3-to 4-day-old American Wistar rat pups according to the procedure described by Sen et al 10 2.4 Confocal imaging to detect activation of p53 by myo and quantitation of cell surface area Isolated rat neonatal ventricular myocytes were stimulated with myo and 5-fluorouracil (5-FU, a potent activator of p53) 18 for 24 h; cell fixation and permeabilization and confocal imaging was performed as described previously 12,19 (see Supplementary material online, Methods). Stimulation of cardiomyocytes with 100 nm Angiotensin II (Sar 1 ) 20 was performed as positive control for the measurement of cell surface area using Image-Pro Plus 6.1 software (see Supplementary material online, Methods).…”
Section: Preparation Of Neonatal Rat Ventricular Myocytesmentioning
confidence: 99%
“…Total RNA was isolated and reverse transcription (RT) PCR analysis was performed following the protocol described previously 12 (see Supplementary material online, Methods).…”
Section: Rna Isolation and Reverse Transcription Pcr For Gene Expression Profilingmentioning
confidence: 99%
“…Consistent with the proposed steric mechanism of CP regulation by V-1, point mutations in the basic patch of CP disrupt both V-1 binding and barbed-end capping 62 . The binding sites on V-1 / myotrophin for CP and for NFkappaB are essentially identical 53,60 , suggesting that V-1 / myotrophin might interact with CP or NFkappaB, but not both. If so, competition between CP and NFkappaB for binding V-1/myotrophin could direct cross-talk between signaling and control of actin assembly.…”
Section: Steric Regulatorsmentioning
confidence: 99%
“…Originally identified as a protein upregulated in the cerebellum during mouse development 54,55 , V-1 was independently linked to cardiac hypertrophy and thus called myotrophin 56-59 . V-1 / myotrophin also interacts with NF-kappaB and co-translocates to the nucleus with p65, which is involved in inducing cardiac hypertrophy 60,61 …”
Section: Steric Regulatorsmentioning
confidence: 99%
“…We have only covered a bit of the biological functions of MTPN. It has been found that MTPN and p65 are co-transported to the nucleus of cardiac myocytes based on the structure of MTPN hairpin, which induces protein synthesis and myocardial growth [35]. Owing to the mechanism of MTPN leading to cell drug resistance is still not clear, it may be the next research direction in CCA.…”
Section: Validation Of Prognostic Values Of Mir-885-5p and Mtpn In Ccamentioning
confidence: 99%